Isolation and identification of multiple drug resistant Neisseria gonorrhoeae from urethritis patients. - Jabbar Salman Hassan; Amir Hani Raziq; Wurood Abdul Salam kadhim (Journal of Madenat Alelem University College, 2016)
Gonorrhea caused by Neisseria gonorrhoeae is one of the most common STIs and is a global health problem because of emerging antibiotic resistant strains that compromise the effectiveness of treatment. This study was carried out to determine the susceptibility and resistance of the most effective antibiotic to Neisseria gonorrhoeae isolated from urethritis patients. Thirty five patients with urethritis were included in this study. Bacterial isolates were identified by standard procedures resistance patterns were detected by disk diffusion test (DDT) and minimum inhibitory concentration (MIC). The minimum inhibitory concentration of all antibiotic used in this study were determined by an agar dilution method as complementary test to the previous sensitivity test to verify the rate of resistance. The results showed that N. gonorrhoeae were completely resistance to cephalexin, gentamicin and trimethoprim with high rate of resistance to rifampicin, doxycycline (84.21%), azithromycin (73.68%) and amikacine (68.42%) and moderate to low rate of resistance to ciprofloxacin (52.63%) and cefotaxime (42.1%). Result showed that N. gonorrhoeae isolates had high rate of sensitivity to levofloxacin and imipenem (94.73%) and 4 out of 19 isolate showed resistances to ceftriaxone with sensitivity rate 78.95%. The present study made to prove that there was only limited number of drugs effective against N. gonorrhoeae, and most probably in near future, if irrational use of antibiotic is not stopped the rate of resistance will increase.